The Economics of Rotating Savings and Credit Associations (ROSCAs) and Poverty in Indonesia - Bayu Kharisma; Sutyastie Soemitro Remi; Ferry Hadiyanto; Andhika Dwi Saputra (Jurnal Economia, 2020)
Abstract: Arisan or Rotating Savings and Credit Associations (ROSCAs) constitute one of the most commonly found informal financial institutions in the developing world. This study aims to analyze the effect of Rotating Savings And Credit Associations (ROSCAs) on poverty in Indonesia using panel data sourced from the fourth and fifth wave of the Family Life Survey (IFLS). This study used a conditional logit or fixed effect logit to see the effect of Rotating Savings and Credit Associations (ROSCAs) participation and control variables, which include individual, household, and community characteristics on poverty variables that are binary or categorized. The results showed that Rotating Savings and Credit Associations (ROSCAs) participation can reduce poverty. Meanwhile, this study shows that women who participate in Rotating Savings and Credit Associations (ROSCAs) can reduce poverty significantly. Keywords: poverty, ROSCAs, IFLS, conditional logit  Ekonomi Arisan dan Kemiskinan di Indonesia Abstrak: Arisan atau Rotating Savings and Credit Associations (ROSCAs) merupakan salah satu lembaga keuangan informal paling umum yang terdapat di negara berkembang. Penelitian ini bertujuan untuk melihat pengaruh arisan (ROSCAs) terhadap kemiskinan di Indonesia dengan menggunakan data panel yang bersumber dari Indonesia Family Life Survey (IFLS) gelombang keempat dan kelima. Metodologi yang digunakan dalam penelitian ini adalah Conditional Logit atau Fixed Effect Logit untuk melihat pengaruh variabel partisipasi arisan dan variabel kontrol yang meliputi karakteristik individu, rumah tangga, dan komunitas terhadap variabel kemiskinan yang bersifat biner atau kategori. Hasil penelitian ini menunjukkan bahwa partisipasi arisan dapat mengurangi kemiskinan. Selain itu, penelitian ini menunjukkan bahwa perempuan yang berpartisipasi dalam arisan dapat mengurangi kemiskinan secara signifikan.  Kata kunci: Kemiskinan, arisan, IFLS, conditional logit